Unexpected threat from conservation to endangered species: reflections from the front-line staff on sea turtle conservation. Issue 12 (2nd December 2017) - Liu, Tzu-Ming
Abstract : This study described the paradox created by the efforts of a conservation organization, which caused an emerging threat to the survival of an endangered species, as well as proposed recommendations to mitigate this paradox. In-depth interviews were conducted to investigate the problems encountered during the implementation of conservation practices by green sea turtle conservation workers (volunteers) in Lanyu, Taiwan. The staff believed that the implementation of the green sea turtle conservation measures violated the traditional cultural beliefs of the local residents (Tao/Yami ethnic group), which caused resentment by the residents towards the organization. Consequently, the residents did not cooperate with the organization and even discouraged conservation activities. In addition, green sea turtle ecotourism promoted by the conservation organization in recent years violated local customs of not having contact with green sea turtles or entering their habitats.